A Dinuclear Ruthenium‐Based Water Oxidation Catalyst: Use of Non‐Innocent Ligand Frameworks for Promoting Multi‐Electron Reactions. Issue 28 (29th April 2015) - Laine, Tanja M.; Kärkäs, Markus D.; Liao, Rong‐Zhen; Siegbahn, Per E. M.; Åkermark, Björn
Abstract Insight into how H2O is oxidized to O2 is envisioned to facilitate the rational design of artificial water oxidation catalysts, which is a vital component in solar‐to‐fuel conversion schemes. Herein, we report on the mechanistic features associated with a dinuclear Ru‐based water oxidation catalyst. The catalytic action of the designed Ru complex was studied by the combined use of high‐resolution mass spectrometry, electrochemistry, and quantum chemical calculations. Based on the obtained results, it is suggested that the designed ligand scaffold in Ru complex 1 has a non‐innocent behavior, in which metal–ligand cooperation is an important part during the four‐electron oxidation of H2O. This feature is vital for the observed catalytic efficiency and highlights that the preparation of catalysts housing non‐innocent molecular frameworks could be a general strategy for accessing efficient catalysts for activation of H2O.